Management of cardiovascular health in acute leukemia: a national survey. Issue 12 (15th October 2019) - Durand, Michelle; Lacaria, Katie; Sidsworth, Margaret; Davis, Margot K.; Sanford, David
Abstract: Cardiovascular (CV) disease is a common comorbidity in acute leukemia (AL) patients and can be worsened by the use of anthracyclines. Interruptions and underutilization of CV medications during AL treatments may negatively impact the CV health of these patients. A 30-question electronic survey was distributed to Canadian hematologists who treat adults with AL to determine the frequency, timing and rationale for interruptions in statins, antiplatelets and angiotensin antagonists in patients undergoing intensive chemotherapy. Strategies for mitigating anthracycline cardiotoxicity, methods of establishing baseline CV risk and utilization of clinical pharmacists were also assessed. Results indicate that it is common for AL patients undergoing intensive chemotherapy to require CV medication interruptions. This highlights the need for collaboration between hematology and cardiology healthcare teams and utilization of multidisciplinary healthcare professionals to improve CV care during AL.